An integrated marketing communications campaign for Ville Sommet Tagaytay - Galvan, Arvin Jasper (Animo Repository, 2016)
Ville Sommet Tagaytay is an estate nestled between Tagaytay and Alfonso, Cavite that provides a venue for celebrations and corporate functions. In the past years, most of the celebrations held at Ville Sommet Tagaytay are Wedding Ceremonies. In a month, Ville Sommet Tagaytay records an average of 4 events. Their main source of booking comes from the website and Facebook, making their online assets effective. This campaign will mainly focus on the Digital Identity and Branding of Ville Sommet Tagaytays Social Media Accounts. First priority is to establish a digital playbook that contains the brands personality, role of its digital assets, rules in target market engagement, and content bucket for Ville Sommet. In order to maximize their Digital Assets, t is also suggested to establish an affinity with its followers on Facebook and Instagram by coming up with contents that are engaging and foster interaction between brand to consumer and consumer to consumer. The campaign is set to run for a total of 6 months, wherein the first month will be utilized to review and implement applicable suggestions that Ville Sommet Tagaytay can use. The campaign is restricted to use 20% of their Annual Income as advertising budget.